The new nature of business the path to prosperity & sustainability - Hoffmann, André; Vanham, Peter 1986- (Ascent Audio, 2024)
In The New Nature of Business: The Path to Prosperity and Sustainability, businessman André Hoffmann and journalist Peter Vanham describe how companies should change their ways to have continued success, and why the current modus operandi is not working. They present a template for creating "sustainable prosperity", and case-studies of companies that survived and thrived by opting for change. In doing so, they provide a way out of long-standing dilemmas, such as how to balance business needs with impact on nature, shareholders with stakeholders, and short-term vs. long-term profits.
Online resource; title from title details screen (O'Reilly, viewed December 10, 2024)
Keywords: Business; Sustainability; Affaires; Durabilité de l'environnement; business (commercial function); Audiobooks; Livres audio